THE ROLE OF EDUCATION AND HYPERTENSION EXERCISES IN IMPROVING THE HEALTH STATUS OF THE COMMUNITY IN BINJAI BARU VILLAGE, KAB. BATUBARA - Nurhayati, Nurhayati; Hasibuan, Fidella Naily Ulya; Faradillah, Faradillah; Hasibuan, Syahrida Suryani; Nurjanah, Della (HEARTY, 2025)
Hypertension is a major risk factor for atherosclerotic cardiovascular disease, heart failure, stroke, and kidney failure. High blood pressure carries the risk of premature death, which increases with the increase in systolic and diastolic blood pressure. This high blood pressure is a very serious problem, as it develops gradually over several years and goes undetected. This activity aims to increase knowledge about hypertension and the community can do hypertension exercises independently to control blood pressure. This research is a quasi- experimental which is experimental in nature. The design used was pre-test and post-test to assess community knowledge before and after counseling. Based on the results of pre-test and post-test conducted with 62 participants, it is known that there is an increase in knowledge where 53 people have good knowledge and 9 others still have less knowledge. The implementation of community service activities went smoothly. It is recommended for the community to routinely check blood pressure to the health center, take medicine regularly, and do hypertension exercises at least 2x a week.